2016
DOI: 10.1371/journal.pone.0148555
|View full text |Cite
|
Sign up to set email alerts
|

Staying Connected on the Road: A Comparison of Different Types of Smart Phone Use in a Driving Simulator

Abstract: Previous research on smart phone use while driving has primarily focused on phone calls and texting. Drivers are now increasingly using their phone for other activities during driving, in particular social media, which have different cognitive demands. The present study compared the effects of four different smart phone tasks on car-following performance in a driving simulator. Phone tasks were chosen that vary across two factors: interaction medium (text vs image) and task pacing (self-paced vs experimenter-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
1
15
1
Order By: Relevance
“…The authors concluded that messaging applications (as opposed to image- or audio-based applications) pose the greatest threat to a driver’s ability to control a vehicle. A similar finding was also reported by McNabb and Gray [ 15 ] who found that image-based applications, such as Instagram and Snapchat, had no significant effect on brake reaction time (BRT) and time headway (TH) variability in a driving simulator study. More specifically, the findings showed that scrolling through and reading the updates from a Facebook account considerably increased BRT and TH variability in a sample of 18 drivers in the USA.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…The authors concluded that messaging applications (as opposed to image- or audio-based applications) pose the greatest threat to a driver’s ability to control a vehicle. A similar finding was also reported by McNabb and Gray [ 15 ] who found that image-based applications, such as Instagram and Snapchat, had no significant effect on brake reaction time (BRT) and time headway (TH) variability in a driving simulator study. More specifically, the findings showed that scrolling through and reading the updates from a Facebook account considerably increased BRT and TH variability in a sample of 18 drivers in the USA.…”
Section: Introductionsupporting
confidence: 86%
“…Our findings indicated that a large proportion of the participants would read and write a text message using mobile phone applications while driving. Because the process of writing / reading text messages using the existing applications, such as Viber and WhatsApp, is exactly the same as writing / reading using a traditional text messaging function, this finding is particularly concerning (e.g., [ 13 , 15 ]). This is because when drivers are actively engaged in texting behaviour, they look 400 times more away from the road [ 25 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was also reported that the drivers drove at a more variable time headway because their ability to respond as rapidly to a leading car gradually altering speed decreased when browsing. Mcnabb & Gray (2016) [86] also observed that messaging and surfing social networking sites on mobile have an adverse effect on driving performance. They observed that brake reaction times and time headway were significantly greater in the texting conditions as compared to both the social media browsing (Facebook, Snapchat, Instagram) conditions and the baseline.…”
Section: Answeringmentioning
confidence: 99%
“…In recent years, the use of driving simulators for the training purposes has become trendy aiming for improving knowledge associated with driving. Moreover, as driving simulators are risk-free and time and cost-effective [25,26], they can be used to simulate the real situation and investigate the impact of drug consumption [26], drowsiness [27], mobile phone [28], adjusting the radio, and searching music on portable devices such as an MP3 [29][30][31][32] on driving style. Observing the behavior of the driver, designing/controlling the vehicle and testing drive systems for driving are amongst the most important investigations performed through employing driving simulators.…”
Section: Introductionmentioning
confidence: 99%